Baslawısh klasslarda ingliz tili pánin oqıtıwda zamanagóy pedagogikalıq texnologiyalardan nátiyjeli paydalanıw (SCIENCE and SOCIETY, 2024)
The article provides opinions and recommendations on the importance of using pedagogical technologies in teaching English in primary schools of secondary schools.